2005
DOI: 10.1144/0016-764904-044
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircon provenance constraints on the evolution of the Harts Range Metamorphic Complex (central Australia): links to the Centralian Superbasin

Abstract: Until recently it has been widely accepted that protoliths to metasediments of the Harts Range Metamorphic Complex (central Australia) were deposited prior to c. 1.75 Ga and form part of the Palaeoproterozoic Arunta Inlier. However, new sensitive high-resolution ion microprobe U-Pb analyses of detrital zircon, together with recently published data, suggest that they were deposited coeval with c. 545-520 Ma sediments from the adjacent, little metamorphosed Neoproterozoic to Palaeozoic Centralian Superbasin. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…The sediment appeared to have been transported over a much longer distance and from an extensive and uniform terrane . As more zircon was analysed, very similar detrital age patterns were found in Ordovician sediments the length and breadth of the Lachlan Fold Belt and in central Australia Buick et al 2005;Williams 1995;Fergusson et al 2007), in Early Paleozoic paragneisses in New Zealand (Ireland 1992;Gibson & Ireland 1996), in Paleozoic sediments of North Victoria Land and Marie Byrd Land, Antarctica, and on Campbell Island south of New Zealand (Ireland et al 1994), in the Kanmantoo Group in South Australia (Ireland et al 1998), in the Malmesbury Group, South Africa (Armstrong et al 1998 and in Early Paleozoic sediments along the Transantarctic Mountains (Goodge et al , 2004Williams et al 2002). All these locations are adjacent to the former proto-Pacific margin of Gondwana, so the distinctive detrital zircon age pattern has become recognised as the signature of the eastern Gondwanan Early Paleozoic (Williams 1995).…”
Section: Provenance Of the Lower Paleozoic Turbiditesmentioning
confidence: 59%
See 2 more Smart Citations
“…The sediment appeared to have been transported over a much longer distance and from an extensive and uniform terrane . As more zircon was analysed, very similar detrital age patterns were found in Ordovician sediments the length and breadth of the Lachlan Fold Belt and in central Australia Buick et al 2005;Williams 1995;Fergusson et al 2007), in Early Paleozoic paragneisses in New Zealand (Ireland 1992;Gibson & Ireland 1996), in Paleozoic sediments of North Victoria Land and Marie Byrd Land, Antarctica, and on Campbell Island south of New Zealand (Ireland et al 1994), in the Kanmantoo Group in South Australia (Ireland et al 1998), in the Malmesbury Group, South Africa (Armstrong et al 1998 and in Early Paleozoic sediments along the Transantarctic Mountains (Goodge et al , 2004Williams et al 2002). All these locations are adjacent to the former proto-Pacific margin of Gondwana, so the distinctive detrital zircon age pattern has become recognised as the signature of the eastern Gondwanan Early Paleozoic (Williams 1995).…”
Section: Provenance Of the Lower Paleozoic Turbiditesmentioning
confidence: 59%
“…Further, inherited zircon in a small intrusion of Devonian (387 Ma) granite had the same age range as the metasediment zircon cores, showing that the Neoproterozoic/ Cambrian metasediment was not a shallow surface layer but extended to the depths of partial melting (Buick et al 2001). Comparison of the protolith zircon ages from the granulites with those from detrital zircon in the lowgrade sediments of the adjacent remnant basins showed that the granulites were in fact high-grade equivalents of some of the lower sediments in the basin sequence (Maidment et al 2004;Buick et al 2005). The tectonic interpretation was that the volcano-sedimentary sequence represented by the granulites was deposited in a Cambrian rift, in places possibly 30 km deep, that once extended half-way across the continent from central Australia to the northwest coast of Western Australia (Maidment et al 2004).…”
Section: Harts Range Metamorphic Complexmentioning
confidence: 95%
See 1 more Smart Citation
“…They are the deformed fill of a huge sedimentary basin (Fig. 12) (Ireland et al, 1998;Fergusson and Fanning, 2002;Black et al, 2004;Buick et al, 2005;Fergusson et al, 2005bFergusson et al, , 2007aMaidment et al, 2007;Greenfield et al, 2010;Glen et al, 2013;Maidment et al, 2013). Pb data is used for age estimates >1Ga.…”
Section: B Cambrian Sedimentation and Delamerian Orogenymentioning
confidence: 99%
“…During the early Ordovician (∼480–460 Ma), sedimentary rocks of Neoproterozoic and Cambrian age in the eastern Arunta Region, on the southern edge of the Georgina Basin, were metamorphosed to granulite facies at depths of 30–35 km and temperatures of ∼800°C [ Mawby et al , 1999; Hand et al , 1999; Buick et al , 2001]. These rocks were subsequently exhumed and juxtaposed against surrounding Paleoproterozoic rocks of the Arunta Region during the earliest phase of the Alice Springs Orogeny (Rodingan Movement) between about 450 and 440 Ma [ Scrimgeour and Raith , 2001; Buick et al , 2005]. This highly localized tectonic episode, termed the Larapinta Event, has been interpreted to result from opening and subsequent closure of a pull‐apart basin in a dextral strike‐slip fault system probably associated with development of the northwest trending Larapintine Seaway [ Buick et al , 2005].…”
Section: Geologic Settingmentioning
confidence: 99%